Effects of polymethylmethacrylate nanoplastics on the swimming behaviour and gut microbiome of the freshwater amphipod Gammarus pulex - Sareh Yaripour; Mandar Bandekar; Jiri Vihavainen; Kuldeep More; Aslak Eronen; Manuela Faria Durão; Mikhail Daneliya; Tuure Houni; Tia Halonen; Jari T.T. Leskinen; Jaakko Haverinen; Hannu Huuskonen; et al. (Ecotoxicology and Environmental Safety)
Plastic pollution has posed a significant environmental concern being widely spread in terrestrial and aquatic ecosystems. Nanoplastic particles (NPs: <1000 nm) have been drawing attention for their potential toxicological implications on organisms. Aquatic animals are increasingly exposed to NPs but their effects on many aquatic invertebrates remain inadequately known. Here, we assessed the effects of 25 nm polymethylmethacrylate NPs on the swimming behaviour and gut microbiome composition of juveniles of an ecologically important detritivore, the Gammarus pulex (Crustacea: Amphipoda: Gammaridae), during a 10-day exposure period at two different concentrations (2 mg/L and 20 mg/L). Our results indicate that NPs treatments may increase swimming behaviour in G. pulex. Moreover, exposure to low concentration of NPs seems to increase bacterial diversity, while high concentration seems to reduce diversity. Taxonomic analysis revealed Rickettsiella and Aeromonas as dominant genera, exhibiting concentration-dependent responses to NPs. The increased swimming activity observed may indicate potential stimulatory effects of NPs on their locomotor behaviour. Additionally, shifts in microbial diversity may indicate the sensitivity of the gut microbiota to environmental stressors, reflecting also potential ecological implications. Further investigation is needed to elucidate the underlying mechanisms driving the detected responses and to assess the potential ecological consequences of NPs pollution on G. pulex in contaminated environments.